2010
DOI: 10.1111/j.1651-2227.2010.02061.x
|View full text |Cite
|
Sign up to set email alerts
|

Becoming baby‐friendly in Spain: a quality‐improvement process

Abstract: Quality-improvement interventions based on participation, training, audit and feedback of information, and provision of resources are useful for the implementation of the BFHI, which is associated with a significant increase in breastfeeding rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 16 publications
2
30
0
6
Order By: Relevance
“…A medical records study conducted in one Turkish hospital covering the first 24 months pp found that BFHI implementation was associated with a 1.5 times increase in breastfeeding duration, but there was no association with EBF across time pp (Duyan Camurdan et al, ). In agreement with this study, a maternity records study conducted in one hospital in Spain found that the median breastfeeding duration increased progressively across time after BFHI programme implementation (Garcia‐de‐Leon‐Gonzalez et al, ).…”
Section: Resultssupporting
confidence: 86%
“…A medical records study conducted in one Turkish hospital covering the first 24 months pp found that BFHI implementation was associated with a 1.5 times increase in breastfeeding duration, but there was no association with EBF across time pp (Duyan Camurdan et al, ). In agreement with this study, a maternity records study conducted in one hospital in Spain found that the median breastfeeding duration increased progressively across time after BFHI programme implementation (Garcia‐de‐Leon‐Gonzalez et al, ).…”
Section: Resultssupporting
confidence: 86%
“…Another gap in the literature is the typical length of time it takes to fully implement the Ten Steps. Only 8 of the articles reviewed 29,62,63,68,70,76,79,84 documented timelines for achieving Baby-Friendly accreditation, which ranged from 1 to 6 years. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, skilled professional and lay interventions provided in the hospital and in community settings during the first days of life have a strong positive influence on both initiation and duration of breastfeeding. 6,7 Improved promotion and support of breastfeeding in maternity facilities and the implementation of the Baby-Friendly Hospital Initiative (BFHI) can therefore be effective interventions. 8 Helping mothers breastfeed also entails assessing the latchon to the breast because this aspect is strongly related to the success of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%